Development of a Modified Ant Colony Algorithm for Order Scheduling in Food Processing Plants - Korobiichuk, Igor; Serhii, Hrybkov; Seidykh, Olga; Ovcharuk, Volodymyr; Ovcharuk , Andrii (Journal of Automation, Mobile Robotics and Intelligent Systems, 2023)
A modified ant colony algorithm has been developed, which, unlike its classical form, when applied to solve the problem of order fulfillment scheduling, allows us to reduce time by using local optimization approaches. The developed modified ant colony algorithm contains an additional improvement by local optimization methods, which reduces the time to find a solution. The proposed algorithm, when applied, allows for reconfiguration of plans while reducing the search time for the optimum by almost 20% compared to other versions of the algorithms.